Z-transform-based FDTD algorithm for anisotropic perfectly matched layer - Ramadan, O (Iee-Inst Elec Eng, 2003)
An efficient method based on the Z-transform theory and the D-H anisotropic perfectly matched layer formulations is presented for truncating general FDTD grids. The formulations are simple and independent of the material properties of the FDTD domain. Numerical examples for radiation and guided-wave problems are included to validate the proposed formulations.